2002
DOI: 10.1046/j.1540-8167.2002.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Atrioventricular Transmission in Mammalian Species: An Evolutionary Riddle!

Abstract: Sealing of A V Transmission. "Sealing deals with the structural and funetional eonsequenees of changes in size or seale among otherwise similar organisms." It plays a key role in all studies on eomparative mammalian physiology and morphology. Heart weight is proportionally related to body weight and ean be described by a straightforward, so-ealled allometrie equation. We studied sealing of A V transmission times (PR intervals on the ECG) in 375 mammals of different dimensions and species. Sealing of A V transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…It may be argued that scaling the PR interval to the BM is limited by the fact that extrapolation of the data to the intercept would result in a PR interval of sizable value for a hypothetical heart of mass 0, which would be meaningless. 7 Clearly, this argument may be legitimate from the point of view of the limitations imposed by the intrinsic properties of a properly working heart, where the mammalian PR interval may never be briefer than a certain limit value because of genetically determined structural, anatomic, and electrophysiological constraints. In fact, on the basis of hemodynamic considerations, West et al 4 calculated that the lowest possible limit of BM for a mammalian species is 1 g. It is therefore worth noticing that allometry describes the relation between the 2 sets of values (eg, BM and HR) only within an observed range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be argued that scaling the PR interval to the BM is limited by the fact that extrapolation of the data to the intercept would result in a PR interval of sizable value for a hypothetical heart of mass 0, which would be meaningless. 7 Clearly, this argument may be legitimate from the point of view of the limitations imposed by the intrinsic properties of a properly working heart, where the mammalian PR interval may never be briefer than a certain limit value because of genetically determined structural, anatomic, and electrophysiological constraints. In fact, on the basis of hemodynamic considerations, West et al 4 calculated that the lowest possible limit of BM for a mammalian species is 1 g. It is therefore worth noticing that allometry describes the relation between the 2 sets of values (eg, BM and HR) only within an observed range.…”
Section: Discussionmentioning
confidence: 99%
“…2 Here, we address the question of whether the time taken by the electrical impulse that propagates across the atrioventricular (AV) conduction system with each heartbeat follows any scaling law. Previous ECG studies in multiple mammalian species, [7][8][9] including humans, have demonstrated that the PR interval, which measures the time taken by an electrical impulse generated in the sinoatrial node to propagate from atria to ventricles, changes by no more than a single order of magnitude when the BM changes by Ϸ6. Meijler et al 7,10 have addressed this question by proposing that the PR interval scales linearly with heart length.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recorded ECG characteristics of the following 28 , and SWR/J. Mice were born, raised, and maintained at The Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…To validate such a premise, and to authenticate the postulate that the scaling exponent of VF frequency vs. BM is Ϫ1/4, we carried out computer simulations of vortex-like reentry in five imaginary species with characteristic heart sizes, L ϭ 1, 2, 4, 8, and 16 cm, covering three orders of magnitude in body size (i.e., BM ϭ 0.017-68 kg). We assumed that the density of these hearts is equal to that of water (1g/cm 3 ) and that their total mass represents 0.6% of the BM (5); consequently, BM ϭ L 3 /0.006 (27). The cell size was assumed to be invariant across species along with the universal formalism of their simple excitation and recovery, for which we used FitzHugh-Nagumo type membrane kinetics [see supporting information (SI) for details].…”
Section: Mechanism Of Ventricular Fibrillation Scalingmentioning
confidence: 99%